The feasibility study towards usage of information technology adoption towards promoting the SMEs products in Kemubu Agricultural Development Authority (KADA) / Ali Zainal Abidin Jalil - Jalil, Ali Zainal Abidin (2012)
The purpose of this research was to identify the use of information technology adoption towards promoting the SMEs product in Kemubu Agricultural Development Authority (KADA). Most of the businesses have now accepted and used information technology application in running their businesses as it become an important tool to increase their business in the domestic as well as global market place. In future IT will grow more rapidly in the Malaysian SMEs sectors. In order to increase the effectiveness of IT, companies can use internet to present almost unlimited information about their products and services in cyberspace. The researcher used simple random sampling, where 100 questionnaire were distributed to the entrepreneur that been guide under KADA. The researcher measured five independent variables which is level of technology, competitor influences, managerial influences, ease of use and cost effectiveness. The dependent variable that been use in this study is information technology adoption. The finding shows that all five independent variables have a relationship with information technology adoption. The method used by the researcher to get these result is by using the regression analysis and P-value approach. Therefore, all SMEs companies that been guide under KADA should use information technology application to improve, increase and enhance their performance as well as their tool to promoting